Assessing the psychometric properties of a modified global wellbeing measure in Ghana - Joseph Kangmennaang; Susan J. Elliott (Wellbeing, Space and Society, 2023)
We live in a world faced by unprecedented environmental change. As such, it is difficult to fathom how we might define, measure, and monitor related impacts on population wellbeing. This is especially the case in low to middle income countries that lack holistic national wellbeing measures but are the most impacted by global environmental changes. As part of a larger research program that aims to develop a Global Index of Wellbeing (GLOWING), this paper reports the assessment of the psychometric properties of a community wellbeing measure, using Ghana as a case study. Informed by the ecosocial and capabilities frameworks and in-depth qualitative and focus group discussions, survey data (n = 1036) were collected from three regions in Ghana to assess population wellbeing across several domains. Using structural equation modelling, psychometric properties of this modified wellbeing measure were tested to show the relative contribution of each domain to overall wellbeing. Pathways between domains and overall wellbeing were also investigated. The modified wellbeing measure showed good sensitivity, validity, and reliability which makes it suitable as a valuable tool for measuring wellbeing in Ghana and perhaps other LMIC settings. Furthermore, while the range of wellbeing constructs showed significance across the three regions studied, their relative importance differed, underscoring the importance of place to the measurement of wellbeing. Multivariate analysis shows a multiple range of factors [living conditions, sense of community, perception of environmental quality and political participation] were associated with wellbeing, requiring innovative, flexible and action-oriented approaches to improving population wellbeing. In this regard, we propose modifications to the scale to enable it to capture the role of place, while allowing for comparisons across space.